Response of two rice cultivars to levels of water in the soil - Vieira, Ana Rita Rodrigues; Steinmetz, Silvio; Brunini, Orivaldo (Pesquisa Agropecuaria Brasileira, 1991)
Experiments were carried out with rice cultivars, to evaluate their behavior when exposed to water stress. The treatments were: 1. soil at field capacity and soil subject to rainfall only during emergence until before flowering and also from final flowering until maturation; 2. irrigated based on of 100, 75, 50, 25 and 0% of maximum evapotranspiration at the flowering stage during the period of 15 days before to 15 days after flowering initiation for CNA-791041 upland. For IR-50 irrigated cultivar this period started 30 to 48 days before flowering. Irrigation started when soil water potential of the reference treatment at 15 cm of depth was -0,010 to -0,015 MPa. Water deficits in the soil was ensured by the use of rain shelters. The results showed: 1. correlation of the yield with the levels and criteria of irrigation as well as the different stage of development when submitted to water deficiency also influenced the results; 2. the cultivar IR-50 showed more negative values of leaf water potential and higher of diffusive resistence to water vapor flux during the period of water stress, presented higher sensibility to water stress.